Manajemen Resiko Gadai Emas Pada UPS PT. Pegadaian Syariah Panyabungan Kota - Mhd Yahya; Dina Aulia Nasution; Annio Indah Lestari Nasution (Universitas Labuhanbatu, 2022)
The background of the research is based on the high level of public interest in Islamic gold pawning products as a result of risk management being the primary focus to be carried out. The risk that often occurs is the risk of being financed, especially the financing of gold pawns. The risk of this gold mortgage financing is the primary focus of UPS PT. Panyabungan Kota Sharia Pawnshop, especially Panyabungan Kota UPS, in conducting data screening for financing applications. This limitation resulted in several stages of financing that were accidentally or intentionally skipped to increase the speed of the financing process.The approach used is already qualitative with the study of the problem method. This study uses primary (primary) and secondary (supporting) data. Information from the main data sources in qualitative research can generally be explored more deeply through observation and interview techniques. As a result of the research, it can be concluded that UPS PT. Panyabungan City Syariah Pawnshop in gold pawn risk management can be from the risk management process, namely, risk, risk measurement, risk monitoring, and risk management. In mitigating especially for gold pawn transactions, namely, including risk of gold diagnosis accuracy, risk mitigation of gold price declines, risk mitigation gold storage. As well as minimizing risks that may occur, namely by monitoring, training and monitoring internal risks.